Variations in Electrocortical Activity due to Surgical Incision in Anaesthetized Cardiac Patients: Electroencephalogram-Based Quantitative Analysis. (1st March 2020) - Kaur, Manpreet; Prakash, Neelam Rup; Kalra, Parveen; Puri, Goverdhan Dutt; Samra, Tanvir; Goyal, Manoj
Abstract : This study examines the alterations in scalp recorded cortical activity due to surgical incision in anaesthetized cardiac patients using electroencephalogram (EEG) patterns. The primary aim was to compare the changes in electrocortical activity after surgical incision. The secondary aim was to compare the changes in time, frequency, and wavelet domain parameters after loss of consciousness (LoC) and after intubation. Real-time EEG data were recorded from 19 patients undergoing cardiac surgery and signals were quantified with time, frequency, and wavelet domain parameters. An increase in hjorth activity, hjorth complexity, rms value, total band power, relative delta band power, standard deviation and maxima of approximation coefficients ( a 5 ), minima of detail coefficients ( d 5, d 4, and d 3 ) and decrease in hjorth mobility; approximate entropy; relative theta, alpha, and beta band power; specentropy; median, spectral edge, and mean frequency; mean of detail coefficients ( d 4 ); standard deviation of detail coefficients ( d 5, d 4, and d 3 ); maxima of detail coefficients ( d 5 ); and minima of approximation coefficients ( a 5 ) were observed during LoC. Decrease in hjorth activity; hjorth mobility; rms value; total band power; relative theta band power; median frequency; standard deviation of coefficients ( a 5, d 5, d 4, and d 3 ); and maxima of coefficients ( a 5, d 5, d 4, and d 3 ) and increase in hjorth complexity; mean of detail coefficients ( d 5 ); and minima of coefficients ( a 5, d 5, d 4, and d 3 ) were observed after intubation. Significant decrease in hjorth activity; hjorth mobility; total band power; relative alpha band power; specentropy; median and mean frequency; standard deviation and maxima of detail coefficients ( d 5, d 4, and d 3 ) and increase in rms value; relative delta band power; mean of coefficients ( a 5 and d 5 ); and minima of coefficients ( d 5, d 4, and d 3 ) were observed due to surgical incision. It can be concluded that different spectral and temporal parameters of EEG signals are highly sensitive to induction, intubation, and surgical incision which are potentially informative for measuring the depth of anaesthesia or efficacy of anaesthetic agents.